1999
DOI: 10.1161/01.atv.19.3.511
|View full text |Cite
|
Sign up to set email alerts
|

Single and Combined Prothrombotic Factors in Patients With Idiopathic Venous Thromboembolism

Abstract: Abstract-The inherited thrombophilias-deficiencies of protein C, protein S, and antithrombin III-and the prothrombotic polymorphisms factor V G1691A and factor II G20210A predispose patients toward venous thromboembolism (VTE). The aim of this study was to determine the prevalence of single and combined prothrombotic factors in patients with idiopathic VTE and to estimate the associated risks. The study group consisted of 162 patients referred for work-up of thrombophilia after documented VTE. The controls wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
140
1
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(152 citation statements)
references
References 62 publications
(48 reference statements)
8
140
1
3
Order By: Relevance
“…22 Others have suggested that this mutation is found in 5% to 15% of patients presenting with venous thrombosis and about 15% of patients being investigated for thrombophilia. 23,24 In my practice, those with a history of DVT had a 17.6% incidence of the defect, those with a history of PE had an 18.2% incidence, and those with current DVT had a 12% incidence of a positive defect.…”
Section: Caprini Et Al Laboratory Markers In Vte I-5mentioning
confidence: 92%
“…22 Others have suggested that this mutation is found in 5% to 15% of patients presenting with venous thrombosis and about 15% of patients being investigated for thrombophilia. 23,24 In my practice, those with a history of DVT had a 17.6% incidence of the defect, those with a history of PE had an 18.2% incidence, and those with current DVT had a 12% incidence of a positive defect.…”
Section: Caprini Et Al Laboratory Markers In Vte I-5mentioning
confidence: 92%
“…Based on various trials, evidence is accumulating that familial thrombophilia, defined as a genetically determined tendency to thrombosis, may be as a result of a combination of clotting defects (Ehrenforth et al, 1999b;Nowak-Go Èttl et al, 1999;Salomon et al, 1999). In particular, evidence has shown that inheritance of FV G1691A combined with deficiencies of protein C, protein S and anti-thrombin, as well as with the PT G20210A variant, the MTHFR T677T genotype in some studies, or enhanced Lp(a) concentrations, further increases the manifestation of early vascular accidents in children and young adults.…”
Section: Risk Factorsmentioning
confidence: 99%
“…This mutation was seen in 5% -15% of different races [13] [15] [16]. Salomon et al studied patients with idiopathic venous thromboembolism (VTE) and reported that the rate of MTHFR-C677T mutation was higher in VTE patients compared to healthy subjects (22.8% vs. 14.3%) [17]. The rate of MTHFR-C677T mutation in CVST patients has been reported to be about 12.5% …”
Section: Mthfr Mutationmentioning
confidence: 99%